1996
DOI: 10.1258/002367796780684926
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of individually housed TO strain laboratory mice for loose substrate or tubes for sleeping

Abstract: SummaryIf we are to improve welfare by appropriate environmental design, it is important to determine which characteristics of prefabricated shelters are preferred by laboratory mice. Three investigations were conducted to determine the preferences of individually housed mice for shape, opacity and openness of tubes for sleeping in. During all three investigations, it was evident that the mice preferred to sleep in sawdust when this was available. The mice slept in the tubes only after the sawdust was removed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…None of the mice constructed nests with sawdust as described previously (Sherwin 1996a). Within 2-3 min of the nesting materials being placed in the cages, many mice had pulled the paper towel from the pot into the main cage, investigated, chewed and manipulated the sheet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the mice constructed nests with sawdust as described previously (Sherwin 1996a). Within 2-3 min of the nesting materials being placed in the cages, many mice had pulled the paper towel from the pot into the main cage, investigated, chewed and manipulated the sheet.…”
Section: Resultsmentioning
confidence: 99%
“…This was despite the mice having no prior experience of these materials or the opportunity to build nests other than heaping sawdust provided as floor substrate (see Sherwin 1996a). This indicates that housing non-breeding mice without nesting materials precludes them from performing a behaviour which is either innate or quickly learnt by a great proportion of laboratory mice (strain and sex differences notwithstanding).…”
Section: Discussionmentioning
confidence: 99%
“…But, there are strain‐dependent responses to tubes, as individually housed male TO mice do not use a tube for sleeping if sawdust is made available as bedding in the cage. Rather, these mice used the tube for refuge and as a latrine …”
Section: Implementing Environmental Enrichmentmentioning
confidence: 99%
“…When sawdust was present (for 11 days), male TO mice (n ¼ 6) preferred to use it to build nests to sleep in than to sleep in any of three available tubes. When sawdust was then removed (12 days), five of the six mice took to sleeping in the tubes, then reverted to sawdust when it was once again made available (Sherwin 1996a). Sherwin (1996b) found that male TO mice (n ¼ 6) defaecated non-randomly in their cages and preferred a substrate with sawdust to a bare plastic floor for this purpose; he concluded that conventional cage designs do not provide mice with a sufficient environment to allow selective hygienic behaviours.…”
Section: Social Behaviourmentioning
confidence: 99%